Analysis of Differences in Stock Trading Volume, Bid-Ask Spread, and Abnormal Returns Before and After a Stock Split: Empirical Evidence from Companies Listed on the Indonesian Stock Exchange - Solo, Yolanda Patricia; Rahmawati, Christina Heti Tri; Purwoto, Lukas (Direktorat Riset dan Pengabdian kepada Masyarakat Universitas Bina Darma, 2024)
A stock split is a company activity carried out in the capital market by splitting the number of shares when the share price does not increase to make it affordable for investors. The research objective is to analyze differences in stock trading volume, bid-ask spread, and abnormal returns before and after the stock split. The research population was all corporations listed on the Indonesia Stock Exchange (BEI) and practicing stock splits in 2018-2022, totaling 42 companies. The research sample included some corporations listed on the IDX and practicing stock splits in 2018-2022 and fulfilling the purposive sampling technique, namely not carrying out other corporate actions in the window period of 5 days before and 5 days after the stock split, totaling 36 companies. The data analysis technique uses the Wilcoxon signed-rank test. The research results show (1) no difference in stock trading volume and bid-ask spread before and after the stock split; (2) there are differences in abnormal returns before and after the stock split. Keywords: Stock Trading Volume, Bid-Ask Spread, Abnormal Return, Stock Split Abstrak Stock split merupakan sebuah aktivitas perusahaan yang dilakukan di pasar modal melalui pemecahan jumlah lembar saham pada saat tidak naiknya harga saham sehingga dijangkau investor. Tujuan penelitian menganalisis perbedaan volume perdagangan saham, bid-ask spread, dan abnormal return sebelum dan setelah stock split. Populasi penelitian semua korporasi yang tercatat di Bursa Efek Indonesia (BEI) dan mempraktikkan stock split tahun 2018-2022 sejumlah 42 perusahaan. Sampel penelitian sebagian korporasi yang tercatat di BEI dan mempraktikkan stock split tahun 2018-2022 serta memenuhi teknik purposive sampling yaitu tidak melakukan aksi korporasi lainnya pada periode jendela 5 hari sebelum dan 5 hari sesudah stock split sebanyak 36 perusahaan. Teknik analisis data menggunakan uji beda wilcoxon signed rank test. Hasil penelitian menunjukkan (1) tidak terdapat perbedaan volume perdagangan saham dan bid-ask spread sebelum dan setelahstock split; (2) terdapat perbedaan abnormal return sebelum dan setelah stock split. Kata kunci: Volume Perdagangan Saham, Bid-Ask Spread, Abnormal Return, Pemecahan Saha